Towards understanding the diversity of banana bunchy top virus in the Great Lakes region of Africa - Niyongere, C.; Lepoint, P.C.E.; Losenge, T.; Blomme, Guy; Ateka, E.M. (Academic Journals, 2015)
The genetic variability of banana bunchy top virus (BBTV) isolates from the Great Lakes region of Africa (GLRA) spanning Burundi, the Democratic Republic of the Congo and Rwanda was assessed to better understand BBTV diversity and its epidemiology for improved disease management. DNA-R and DNA-S fragments of the virus genome were amplified and sequenced in this study. These two BBTV fragments were previously used to classify isolates into the South Pacific and the Asian groups. Phylogenetic analyses based on nucleotide sequences involving GLRA isolates and those obtained from the GenBank database were carried out. Sequence similarity for both DNA-R and DNA-S fragments ranged between 99.1 to 100.0% among the GLRA isolates, 96.2 to 100.0% and 89.7 to 94.3% between the GLRA isolates and those previously clustering in the South Pacific and the Asian groups, respectively. These results showed that GLRA isolates belong to the South Pacific group and are phylogenetically close to the reference Indian isolate. The similar banana cultivars and BBTV isolates across the GLRA implied that the disease may have mainly spread through exchange of planting material (suckers) between farmers. Thus, farmers' awareness and quarantine measures should be implemented to reduce BBTV spread in the GLRA.